Graduates of Higher Education in the Food and Agricultural Sciences: An Analysis of Supply/Demand Relationships. Volume I Agriculture, Natural Resources, and Veterinary Medicine - Science and Education Administration (USDA), Hyattsville, MD.; Coulter, Kyle Jane; Stanton, Marge; Science and Education Administration (USDA), Hyattsville, MD. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1980)
Information on the current and projected supply of and demand for graduates of higher education in the food and agricultural sciences is presented, based on federal data bases. The supply data are aggregated by 11 educational clusters, and employment demand data are aggregated by eight occupational clusters. Analysis reveals imbalances in the supply of, and demand for, graduates of higher education in the food and agricultural sciences. When total supply is related to total demand for each of the eight occupational clusters, shortages of qualified graduates appear to exist through 1985 for five clusters: scientific and professional specialists, manufacturing and processing scientists and engineers, sales and service representatives and purchasing agents, administrators/managers/financial advisors, and miscellaneous agricultural specialists. Supply approximates demand for agricultural production and management specialists, and exceeds demand for media specialists and educators. However, several supply deficiencies were identified for educators. Information is presented on supply/demand relationships by occupational cluster, degree type (agriculture and agriculture-related), and degree level (associate, baccalaureate, master's, doctoral, and Doctor of Veterinary Medicine). Suggestions for future research on this topic are presented, and additional information is included on international employment opportunities for food and agricultural graduates. Findings pertinent to data collection for the Foreign Agricultural Service and those stemming from the review of existing data are discussed. (SW)
Availability: Office of Higher Education, Science and Education Administration, United States Department of Agriculture, Washington, DC 20250.
ERIC Note: Best copy available.
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Agribusiness; Agricultural Chemical Occupations; Agricultural Engineering; Agricultural Occupations; Agricultural Supply Occupations; Animal Husbandry; Botany; College Graduates; Demand Occupations; Dietetics; Employment Opportunities; Employment Patterns; Employment Projections; Food; Higher Education; Off Farm Agricultural Occupations; Soil Science; Veterinary Medicine; Reports, Research; Numerical/Quantitative Data